Evaluasi Strategi Promosi Pendaftaran Sekolah Bagi Calon Siswa dengan Metode SWOT di SMK Al Mafatih Jakarta - Samdrina Junaedi; Asrul Sani (Pusat Riset dan Inovasi Nasional, 2025)
The school admission promotion strategy for new students is carried out with an integrated approach to attract the interest of parents and students. The promotion includes disseminating information through social media, the school's official website, brochures, and cooperation with educational institutions and local communities. This study aims to determine the effectiveness of the school registration promotion strategy using SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. This method is used to identify internal strengths and weaknesses, as well as external opportunities and threats that affect the success of the promotion. The results of the study indicate that digital-based promotion strategies such as social media and websites have a wide reach, but still need to be improved in terms of content and interactivity. Meanwhile, cooperation with local communities has a positive impact on building public trust. The conclusion of the SWOT analysis shows that schools need to optimize their strengths and anticipate threats so that the promotion strategy is more effective and sustainable.